Corruption in the Perspective of the Qur'an and Tripitaka (Comparative Study of Sacred Texts) - Muhammad Imam Syafi’i (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
One of the most important moral and social problems facing the world today is corruption. Corruption erodes people's trust in the institutions that are supposed to serve and protect them, as well as the integrity of political and economic systems. The purpose of this article is to examine corruption from the perspective of Islamic scriptures and Buddhist scriptures, using a comparative study. The conclusion of this study The two main religions, Islam and Buddhism, both condemn corruption as an act that harms society and a violation of moral standards. The essential message of all religions is the same, despite differences in vocabulary and methods: justice, honesty and integrity are important qualities to uphold.